Effectiveness, complications, and reproductive outcomes after cesarean scar pregnancy management: a retrospective cohort studyAJOG Global Reports at a Glance - Carry Verberkt, MD; Marike Lemmers, MD, PhD; Robert A. de Leeuw, MD, PhD; Norah M. van Mello, MD, PhD; Freek A. Groenman, MD, PhD; Wouter J.K. Hehenkamp, MD, PhD; Judith A.F. Huirne, MD, PhD (Elsevier, 2023)
BACKGROUND: There is a dramatic rise in cesarean deliveries worldwide, leading to higher complication rates in subsequent pregnancies. One of these complications is a cesarean scar pregnancy. During the last decades, treatment options for cesarean scar pregnancies have changed, and less invasive interventions have been employed to preserve fertility and reduce morbidity. However, the optimal treatment approach and the influence of various treatments on reproductive outcomes have to be determined. OBJECTIVE: This study aimed to evaluate the short- and long-term outcomes after cesarean scar pregnancy management. STUDY DESIGN: We conducted a retrospective cohort study of women determined to have a cesarean scar pregnancy from 2010 to 2021 at a tertiary referral center, the Amsterdam University Medical Center, in the Netherlands. Outcomes of the following management strategies were compared: expectant management, methotrexate, curettage with temporary cervical cerclage, or a laparoscopic niche resection. We performed a curettage if the cesarean scar pregnancy did not cross the serosal line of the uterus, and a laparoscopic niche resection was performed if the cesarean scar pregnancy crossed the serosal line. The main outcomes were treatment efficacy and time to subsequent ongoing pregnancy or pregnancy leading to a live birth. RESULTS: Of the 60 included women, 5 (8.3%) were managed expectantly, 8 (13.3%) were treated with methotrexate, 31 (51.8%) were treated with a curettage, and 16 (26.7%) with a laparoscopic niche resection. The groups were not comparable. The gestational age and human chorionic gonadotropin levels were generally higher in women who received methotrexate or a laparoscopic niche resection. Additional treatment in the conservative group was needed for 4 (80%) women after expectant management and for 7 (87.5%) women after methotrexate treatment. In the surgical group, all 31 women treated with a curettage and all 16 treated with a laparoscopic niche resection did not require additional treatment. The subsequent ongoing pregnancy rate after cesarean scar pregnancy management was 81.1% (30/37) among women who wished to conceive, with a live birth rate of 78.4% (29/37); 1 woman was in her third trimester of pregnancy at the time of analyses. The time between cesarean scar pregnancy management and subsequent ongoing pregnancy was 4 months (interquartile range, 3-6; P=.02) after expectant management, 18 months (interquartile range, 13-22) after initial methotrexate treatment, 5 months (interquartile range, 3-14; P=.01) after a curettage, and 6 months (interquartile range, 4-15; P=.03) after a laparoscopic niche resection. CONCLUSION: Surgical treatment of a cesarean scar pregnancy led to a high success rate without additional interventions, high pregnancy rates with a short time interval between treatment, and subsequent pregnancy leading to an ongoing pregnancy or live birth. Conservative management, both with expectant management and methotrexate treatment, led to high (re)intervention rates. Different management approaches are indicated for different types of cesarean scar pregnancies.